DEVELOPMENT OF ELECTRONIC MODULE BASED ON INTERACTIVE LECTURE DEMONSTRATIONS WITH MICROSOFT SWAY ON DIRECT CURRENT ELECTRICAL CIRCUIT - Aulia Maharani; Sunaryo Sunaryo; I Made Astra (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
Abstrak Seiring dengan perkembangan IPTEK di bidang pendidikan, bahan ajar dapat dibuat berbasis teknologi. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan modul elektronik fisika berbasis interactive lecture demonstrations (ILD) berbantuan Microsoft Sway pada materi rangkaian listrik arus searah untuk siswa SMA kelas XII. Penelitian ini dilakukan dengan menerapkan metode Research and Development (R&D) dengan menggunakan model ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Berdasarkan hasil survei yang dilakukan di kelas XII MIPA SMAN 3 Kabupaten Tangerang terhadap 34 siswa, hasil yang didapat menunjukkan bahwa sebanyak 85,3% siswa mengalami kesulitan dalam memahami materi fisika, 76,5% siswa tertarik mempelajari fisika menggunakan modul elektronik, dan 100% siswa tertarik mempelajari fisika melalui demonstrasi. Modul elektronik yang dikembangkan didesain dengan menerapkan model pembelajaran Interactive Lecture Demonstrations (ILD). Pada setiap kegiatan belajar terdapat tahapan model pembelajaran Interactive Lecture Demonstrations (ILD) yaitu diawali dengan tahap predict, selanjutnya dilanjutkan dengan tahap experience, dan diakhiri dengan tahap reflect. Kata-kata kunci: modul elektronik, ILD, Microsoft Sway, fisika, rangkaian listrik arus searah Abstract The problem-solving skills of students in the 21st century and the need for electronic teaching materials are the reasons for this research. These problems solving skills can be trained in practical activities. In this case, a sound wave electronic student worksheet was made according to the results of observations of field needs to produce electronic student worksheets based on problem-solving using Flip PDF Professional application on sound wave material to help students study independently due to the pandemic that caused changes in systems outside the network to become networked. The method used in this research is research and development (R&D) with the ADDIE approach. This article describes the use of the Flip PDF Professional support application and the content according to the problem-solving stages. This electronic student worksheet presents multimedia as a stimulus. Students are asked to answer preliminary and final knowledge tests, conduct simple experiments according to the work steps, create experimental observation tables, and process data and concepts regarding related experimental material. The data was collected using a questionnaire, revised by the researcher regarding material content and appearance, and processed using the effect size formula. This electronic student worksheet was declared feasible regarding material and learning media by validators training HOTS students through student problems solving skills. Keywords: electronic module, ILD, Microsoft Sway, physics, direct current electrical circuit